2014
DOI: 10.1017/s1368980014001396
|View full text |Cite
|
Sign up to set email alerts
|

Opposites don’t attract: high spouse concordance for dietary supplement use in the European Prospective Investigation into Cancer in Norfolk (EPIC-Norfolk) cohort study

Abstract: Objective: Dietary supplements are commonly consumed but may not be beneficial for everyone. It is known that supplement users have healthy behaviour characteristics but until now concordance between spouses living in the same household has not been investigated and concordance may be an important behavioural determinant. Design: Prospective cohort study, cross-sectional data analysis. Setting: European Prospective Investigation into Cancer in Norfolk (EPIC-Norfolk) in the UK, recruitment between 1993 and 1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The second theory alludes to spouses converging in their behaviors and lifestyle over the course of the marriage as a result of engaging in similar activities, practices, and habits [42,14,15]. In support of both theories, substantial spousal resemblance has been reported for blood pressure [43], glucose [5,6], lipids [9], physical activity [44,45], sedentary lifestyle [46], diet and eating patterns [47,48], dietary supplement use [49], sleeping patterns [50] and smoking [48]. For instance, having an obese spouse is reported to be associated with a 37% to a 2-fold risk of obesity in the other spouse [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The second theory alludes to spouses converging in their behaviors and lifestyle over the course of the marriage as a result of engaging in similar activities, practices, and habits [42,14,15]. In support of both theories, substantial spousal resemblance has been reported for blood pressure [43], glucose [5,6], lipids [9], physical activity [44,45], sedentary lifestyle [46], diet and eating patterns [47,48], dietary supplement use [49], sleeping patterns [50] and smoking [48]. For instance, having an obese spouse is reported to be associated with a 37% to a 2-fold risk of obesity in the other spouse [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…In a follow up study, the risk of age related cataract was investigated in Swedish men and revealed that the use of multiple supplements in combination with vitamin C was not associated with cataract risk, but that the use of high dose vitamin C may increase the risk of cataract [ 118 ]. The use of dietary supplements in the form of multivitamins or a specific vitamin is widespread ranging from 22% to 53% in studies conducted from USA, Canada, Korea, UK, Sweden, Germany, and France [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. While these supplements are taken for a range of health reasons, based on findings from the above clinical trials, the long-term value of vitamin C supplementation in decreasing the risk of cataract progression is questionable, and at high doses may in fact exacerbate cataract progression.…”
Section: Evidence Of the Effects Of Vitamin C On Cataract Preventimentioning
confidence: 99%
“…At the same time, the role of traditional and complementary medicine (T&CM) has also gained attention around the globe, being an alternative to the conventional medicine in healthcare system. About 40.2% of U.K. adults (1) and 52% of U.S. population (2) reported health supplements use, while 16.4% of Japanese mothers provided health supplements to their children (3). Apart from that, T&CM medicine usage is also common among the U.S. population, where 17.7% of them had used nonvitamin, nonmineral, or natural products in 2007 (4).…”
Section: Introductionmentioning
confidence: 99%